From the Classroom to the Living Room: Home-Based Learning to Improve Students’ Achievement in English Learning amid Pandemic - Kamaliasari; Nurbianta (The Indonesian Institute of Science and Technology Research, 2022)
The goal of the study was to see how successful Home-Based Learning (HBL) is for senior high school students during Corona Virus Disease 2019 (Covid-19). The researcher looked at the students' performance in pre-test and post-test between the controlled and experimental groups, as well as the significant difference between the two groups, to determine effectiveness. The study used a quantitative design, the students were placed into two groups for data collection: the controlled group and the experimental group. A pre-test and a post-test were given to both groups. The normality distribution test, homogeneity variance test, paired sample correlation test, and to test the effectiveness of HB. The hypotheses testing was needed, therefore paired sample t-test was used to examine the raw data. According to the calculations, the experimental group's post-test mean score was 64.33, compared to 46.00 for the control group. In addition, the paired sample t-test is used to assess hypotheses. The significant value was calculated using SPSS 16.0 and was found to be (3.800>2.145). This demonstrated that the home-based learning program was successful. This research was significantly unique as it did not only focus on the causes of online home-based learning but brought into light its effectiveness.